Negative-pressure wound therapy in combination with bronchial occlusion to treat bronchopleural fistula: a case report - Masashi Iwasaki; Masanori Shimomura; Tsunehiro Ii (Surgical Case Reports)
Abstract Background Bronchopleural fistula, which usually accompanies bronchial fistula and empyema, is a severe complication of lung cancer surgery. Negative-pressure wound therapy can enhance drainage and reduce the empyema cavity, potentially leading to early recovery. This therapy is not currently indicated for bronchopleural fistulas because of the risk of insufficient respiration due to air loss from the fistula. Case presentation A 73-year-old man, who was malnourished because of peritoneal dialysis, was referred to our hospital for the treatment of lung cancer. Right lower lobectomy with mediastinal lymph node dissection was performed via posterolateral thoracotomy, and the bronchial stump was covered with the intercostal muscle flap. His postoperative course was uneventful and he was discharged. However, he was readmitted to our hospital because of respiratory failure and diagnosed as having bronchopleural fistula on the basis of the bronchoscopic finding of a 10-mm hole at the membranous portion of the inlet of the remnant lower lobe bronchus. Thus, thoracotomy debridement and open window thoracostomy were immediately performed. After achieving infection control, bronchial occlusion was performed using fibrin glue and a polyglycolic acid sheet was inserted through a fenestrated wound. Bronchial fistula closure was observed on bronchoscopy; therefore, a negative-pressure wound therapy system was applied to close the fenestrated wound. The collapsed lung was re-expanded and the granulation tissue around the wound increased; therefore, thoracic cavity size decreased and thoracoplasty using the latissimus dorsi was performed. Conclusions This bronchopleural fistula was treated successfully after a right lower lobectomy using an extra-pleural bronchial occlusion and negative-pressure wound therapy.